THE IMPACT OF COVID-19 ON CONSUMER’S SHOPPING TRIP PATTERN - Alfi Rizka Thoriq; Nahry (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2022)
Abstract The Covid-19 pandemic has significantly affected the lives of all people in the world, with many people staying at home so that online stores are one of the places of choice for shopping. Before the Covid-19 pandemic, consumers carried out shopping activities with 2 methods, conventional shopping or trips to the store and online shopping. This change affects the transportation sector so research is needed on changes in consumer’s shopping trip patterns due to Covid-19 which aims to analyze changes in consumer’s shopping trip patterns due to the Covid-19 pandemic, post Covid-19 pandemic, the potential end of Covid-19, and the potential effects of Covid-19 interventions, before, during, and after Covid-19 ends, for 2 shopping commodities, namely gro-cery and fashion. This study shows that the Covid-19 pandemic has had an impact on changes in consumer’s shopping trip patterns in each aspect, those are the frequency of conventional shopping trips, modes of trip, types of trip and the frequency of consumer online shopping, but with significant differences for each group of consumer characteristics. To anticipate changes in consumer’s shopping trip patterns after the Covid-19 pande-mic, city transportation authorities should adjust urban transportation planning in its modeling to be more accurate, especially in planning related to last-mile delivery vehicles and city logistics. Keywords: shopping activities; conventional shopping; online shopping; shopping trip pattern; Covid-19 pandemic. Abstrak Pandemi Covid-19 berdampak signifikan terhadap kehidupan seluruh masyarakat di dunia, dengan banyaknya masyarakat yang berdiam diri di rumah, sehingga toko online menjadi salah satu tempat pilihan untuk berbelanja. Sebelum adanya pandemi Covid-19, konsumen melakukan aktivitas belanja dengan 2 metode, yaitu belanja konvensional atau melakukan perjalanan ke toko dan belanja online. Perubahan ini berdampak pada sektor transportasi, sehingga diperlukan penelitian tentang perubahan pola perjalanan belanja konsumen akibat Covid-19, yang bertujuan untuk menganalisis perubahan pola perjalanan belanja konsumen akibat pandemi Covid-19, pasca pandemi Covid-19, potensi berakhirnya Covid-19, dan potensi dampak intervensi Covid-19 sebelum, selama, dan setelah Covid-19 berakhir untuk 2 komoditas belanja, yaitu bahan makanan dan fesyen. Penelitian ini menunjukkan bahwa pandemi Covid-19 berdampak pada perubahan pola perjalanan belanja konsumen di setiap aspek, yaitu frekuensi perjalanan belanja konvensional, moda perjalanan, jenis perjalanan dan frekuensi belanja online konsumen, dengan perbedaan yang signifikan untuk masing-masing kelompok karakteristik konsumen. Untuk mengantisipasi perubahan pola perjalanan belanja konsumen pascapandemi Covid-19, otoritas transportasi kota harus menyesuaikan perencanaan transportasi perkotaan dalam pemodel-annya agar lebih akurat, terutama dalam perencanaan yang terkait kendaraan pengiriman akhir atau last mile dan logistik kota. Kata-kata kunci: aktivitas berbelanja; belanja konvensional; belanja online; pola perjalanan belanja; pandemi Covid-19.